The Effect of Employing the Kagan Strategy in Learning Arabic for Non-Native Students - Altlouhi, Raad Jamal (Journal of Curriculum and Teaching Methodology, 2022)
The study aims to identify the characteristics of teachers of Arabic for non-native speakers, to reveal the difficulties that teachers face in teaching Arabic to non-native speakers, to identify the theoretical literature that dealt with the impact of employing Keegan’s strategy in learning Arabic for non-native speakers, and to identify the principles The basics of Keegan's strategy, and its structures, the study relied on the experimental method and the descriptive analytical approach. The study used a pre and post achievement test on non-Arabic speaking students in private schools in the State of Qatar and preparing lessons according to Keegan's strategy. Their strength in the control group was four students and the experimental group was four students, and it concluded The results of the study indicated that there were statistically significant differences between the scores of the experimental group students who studied the Arabic language subject before and after the achievement test, and there were statistically significant differences between the scores of the experimental group students who studied the Arabic language according to Keegan’s structures attributed to the age group variable, and the study recommended a group of The most important recommendations are: Work to reduce the difficulties that educators and managers face For schools to employ new learning strategies to teach non-Arabic speaking students and provide its requirements to achieve its desired goals, and to provide training and qualification courses for Arabic language teachers in schools, whether governmental or private, to promote modern strategies in learning for non-Arabic speaking students.
Keywords: Kagan strategy; Kagan structures; Cooperative learning; Non-Arabic speaking students